Perthite in nepheline syenite from the kakortokite unit in the Ilimaussaq Complex, south Greenland - Schønwandt,H.K.; Barnes,G.B.; Ulrich,T. (Journal of Geosciences, 2023)
Petrographic investigations of white kakortokite (nepheline syenite) reveal two structurally different types of perthite grains, herein called type A and B. Type A is more common and consists of an intimate intergrowth of microcline and albite. Microcline in type A perthites consists of two irregular penetrative individuals which appear as elongated pointed bodies parallel to (010) intergrown with polysynthetic twinned albite, which occurs as serrated bodies elongated parallel to (010). In type B perthites, K-feldspar (microcline) shows tiled structure and albite appears as microcrystalline equigranular veinlets, penetrating the perthite grain often perpendicular to (010). A great compositional variation of the type A grains (from nearly 100% microcline to almost pure albite) excludes exsolution to be the main process responsible for the structure. On the other hand, a replacement process controlled by a simultaneous dissolution-precipitation can explain the structure of type A, which means that widespread Na-metasomatism (albitization) had to have taken place in the kakortokite. Due to the different twinning structure of K-feldspar (microcline) in type B, the albitization in these grains occurred by albite veining of the grains.
Keywords: perthite; Ilimaussaq; kakortokite; Na-metasomatism; peralkaline rocks